Problemy modelowania niezawodności sieci transportowych - Nowakowski, Tomasz (Problems of Transportation Net Reliability Assessment, 2005)
The article proves the usefulness of transport net reliability assessment. The example of reliability assessment of transport objectives realization in a forwarding firm is presented the base of theoretical assessment of transport nets reliability with the use of among others operating paths is discussed. The calculations is done for one transport net.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1078, s. 130-139